PENGARUH PERAN SERTA SUAMI TERHADAP TINGKAT KECEMASAN IBU HAMIL DALAM MENGHADAPI PROSES PERSALINAN DI DESA TEJOASRI KECAMATAN LAREN KABUPATEN LAMONGAN 2015 - Mimatun Nasihah; Ninis Nur Hidayah (Jurnal MIDPRO, 2015)
A marriage not yet complete without attendance of a child, so that the spouse will be non-stop to try to get a child. Wiknjosastro (1994), having a notion that feeling pain in bone in bearing always become a talking point since former, hence a lot of mother which face on pregnancy and bearing with feeling fear and worry. This research aim is to know how big influence of husband role to level dread of pregnant mother in face of process of bearing in Village of Tejoasri, Sub district of Laren, Regency of Lamongan. Subject of this research are pregnant mother and her husband.Methods : Participation of husband since the early of pregnancy will facilitate the couple in experiencing and overcoming various changes that happened at body as effect of attendance of dinky human in stomach. Even, with husband participation from the early pregnancy until the bearing time arrive can lessen fear and dread of mother in face of bearing, it is very determined by how big his role and participation in pregnancy period and attention of husband in trimester I until trimester III. Level of this dread is laid open using ASS dread scale in face of bearing process. Type of this research is a correlation descriptive quantitative research.Result : From regression analyzes result is found that there are influence which very significant between husband participation to level dread of pregnant mother in face of bearing process. Table 4.11 explained that F count > F table ( 9.036 > 6.24) significant with 0.006 < 0.05, 9.036 > 0.249 significant by 0,006 < 0,001 so that inferential that there is influence between husband participation to the level dread of pregnant mother in face of bearing process in Village of Jepat Lor, hence this hypothesis is provenKeywords: Husband Participation and Level Dread of Pregnant Mother in Face of Bearing Proces